Hidden psychopharmacology: how non-psychotropic drugs modulate emotions and implications for clinical practice - Чорномидз, Андрій; Чорномидз, Ірина; Чорномидз, Юрій (Psychosomatic Medicine and General Practice, 2025)
This article provides a comprehensive analysis of the impact of drugs traditionally classified as "non-psychotropic" on emotional state, mood, and cognitive-affective regulation. It reviews the neurobiological mechanisms by which somatic medications modulate mental functions, including their influence on neurotransmitter systems (GABA, glutamate, serotonin, dopamine), the hypothalamic-pituitary-adrenal (HPA) axis, neuroinflammation, cytokine pathways, and the microbiome. The clinical profiles of key pharmacological groups are analyzed in detail: corticosteroids (induction of mania and depression), isotretinoin (effects on neurogenesis and mood), beta-blockers (modulation of the peripheral component of fear and memory reconsolidation), fluoroquinolones (anxiety and dissociation via GABA blockade), hormonal contraceptives (hormonal vulnerability), NSAIDs and acetaminophen (emotional blunting and anti-inflammatory antidepressant effects), antihistamines, and immunomodulators. Special attention is given to the concept of "emotional pharmacology," which views these effects not merely as adverse reactions but as potential therapeutic targets (e.g., using anti-inflammatory agents for treatment-resistant depression or beta-blockers for PTSD). The article concludes that an interdisciplinary approach is essential for monitoring the mental health of somatic patients and for personalizing therapy based on genetic and immune risk factors. Keywords: non-psychotropic drugs, drug-induced mood disorders, neuroinflammation, psychopharmacology, emotional regulation, adverse psychiatric effects.